Comparing Autologous to Device-Based Breast Reconstruction: A Pilot Study of Return in Breast Sensation. (May 2022) - Huang, Hao; Wang, Marcos Lu; Ellison, Angela; Otterburn, David M.
Abstract : Background: Poor breast sensation is common after mastectomy and reconstruction. In this study, we aim to define the temporal pattern of sensory changes after reconstruction and to compare the return in sensation between autologous and device-based reconstruction. Methods: Women undergoing mastectomy with immediate reconstruction, with either tissue expander (TE) or neurotized deep inferior epigastric perforator (DIEP) flap, were prospectively identified at their preoperative or postoperative visit at defined time points. Neurosensory testing was performed in 9 breast regions using the AcroVal pressure-specified sensory device to determine 1 point-static cutaneous thresholds. Sensitivity data were averaged between patients at each time point and plotted over time. Results: Eighty-seven patients (153 breasts) were included in this study, including 41 women (75 breasts) with DIEP flap and 46 women (78 breasts) with TE. The groups were comparable in age, body mass index, breast size, chemotherapy, radiotherapy, and number of revisional breast surgeries ( P > 0.05). Compared with preoperative baseline, mean cutaneous thresholds in DIEP flap patients were comparable in most outer breast regions at 18 months postoperatively and in the entire breast, except the inner inferior region, at 3 years ( P > 0.05). In contrast, mean cutaneous thresholds in TE patients continued to be significantly worse in the entire breast at 5 years postoperatively compared with baseline ( P < 0.05). Conclusions: Autologous breast reconstruction is superior in sensory recovery. Patients undergoing DIEP flap can expect sensory return to preoperative levels by 3 years, with sensation returning by 18 months in some areas of the breast. Patients undergoing device reconstruction should expect a slower and more unpredictable return in breast sensation.